Status of digital filmmaking in the Philippines. - Ayuste, Ira Sheena C.; Guda, John Mark.; Noveros, John Trexy (2006.)
The Philippines was once considered to be the one of the most prolific filmmakers in Asia, second to Hollywood in India. But Philippine film industry suffered decline in number of film productions. Because of the advancement of technology, independent filmmakers started to work on digital films. Year 2005 considered to be the peak digital filmmaking in the country. Numerous independent digital films were produced and some were given international and awards. However, digital films strongest components are its relevant societal themes and storyline and new film treatment and creative freedom. It primarily targets and develops a new set of audience, who basically belong to today's generation as digital filmakers claimed to be the voice of the new generation on how they see life, the society and the world. However, with the continous struggle to educate the viewing public, with the help of different sectors, digital filmmaking has the potential to compete with commercial films in terms of volume of viewer ship, eventually contributing to the increase of film production in the Philippine Film Industry.
Thesis (Undergraduate, Bachelor of Science in Broadcast Communication) College of Arts and Sciences, University of the Philippines Visayas, Miag-ao, Iloilo
Keywords: Digital filmmaking -- Philippines